2020
DOI: 10.1186/s12888-020-02919-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary care and mental health providers’ perceptions of implementation of pharmacogenetics testing for depression prescribing

Abstract: Background Pharmacogenetic testing (PGx) has the potential to improve the quality of psychiatric prescribing by considering patients’ genetic profile. However, there is limited scientific evidence supporting its efficacy or guiding its implementation. The Precision Medicine in Mental Health (PRIME) Care study is a pragmatic randomized controlled trial evaluating the effectiveness of a specific commercially-available pharmacogenetic (PGx) test to inform antidepressant prescribing at 22 sites acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 23 publications
4
40
0
2
Order By: Relevance
“…Of the included studies, seven were conducted in the United States ( Shishko et al, 2015 ; Thompson et al, 2015 ; Goodspeed et al, 2019 ; Liko et al, 2020 ; McCarthy et al, 2020 ; Vest et al, 2020 ; Kastrinos et al, 2021 ), with the remaining studies being conducted in Canada ( Walden et al, 2015 ), France ( Laplace et al, 2021 ), Singapore ( Chan et al, 2017 ), and New Zealand ( Dunbar et al, 2012 ). Three of the studies gathered patient perspectives about PGx ( Liko et al, 2020 ; McCarthy et al, 2020 ; Kastrinos et al, 2021 ), while the remaining studies gathered HCPs viewpoints on PGx ( Dunbar et al, 2012 ; Shishko et al, 2015 ; Thompson et al, 2015 ; Walden et al, 2015 ; Chan et al, 2017 ; Goodspeed et al, 2019 ; McCarthy et al, 2020 ; Vest et al, 2020 ; Laplace et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, seven were conducted in the United States ( Shishko et al, 2015 ; Thompson et al, 2015 ; Goodspeed et al, 2019 ; Liko et al, 2020 ; McCarthy et al, 2020 ; Vest et al, 2020 ; Kastrinos et al, 2021 ), with the remaining studies being conducted in Canada ( Walden et al, 2015 ), France ( Laplace et al, 2021 ), Singapore ( Chan et al, 2017 ), and New Zealand ( Dunbar et al, 2012 ). Three of the studies gathered patient perspectives about PGx ( Liko et al, 2020 ; McCarthy et al, 2020 ; Kastrinos et al, 2021 ), while the remaining studies gathered HCPs viewpoints on PGx ( Dunbar et al, 2012 ; Shishko et al, 2015 ; Thompson et al, 2015 ; Walden et al, 2015 ; Chan et al, 2017 ; Goodspeed et al, 2019 ; McCarthy et al, 2020 ; Vest et al, 2020 ; Laplace et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, seven were conducted in the United States ( Shishko et al, 2015 ; Thompson et al, 2015 ; Goodspeed et al, 2019 ; Liko et al, 2020 ; McCarthy et al, 2020 ; Vest et al, 2020 ; Kastrinos et al, 2021 ), with the remaining studies being conducted in Canada ( Walden et al, 2015 ), France ( Laplace et al, 2021 ), Singapore ( Chan et al, 2017 ), and New Zealand ( Dunbar et al, 2012 ). Three of the studies gathered patient perspectives about PGx ( Liko et al, 2020 ; McCarthy et al, 2020 ; Kastrinos et al, 2021 ), while the remaining studies gathered HCPs viewpoints on PGx ( Dunbar et al, 2012 ; Shishko et al, 2015 ; Thompson et al, 2015 ; Walden et al, 2015 ; Chan et al, 2017 ; Goodspeed et al, 2019 ; McCarthy et al, 2020 ; Vest et al, 2020 ; Laplace et al, 2021 ). Data collection methods varied with some studies opting for focus groups ( Goodspeed et al, 2019 ; Vest et al, 2020 ), while one conducted semi-structured interviews ( Liko et al, 2020 ) and other studies collected data using a survey ( Shishko et al, 2015 ; Thompson et al, 2015 ; Walden et al, 2015 ; Kastrinos et al, 2021 ) or questionnaire ( Dunbar et al, 2012 ; Chan et al, 2017 ; McCarthy et al, 2020 ; Laplace et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a specialist believes the primary care physician should act on the pharmacogenetic results, and vice versa, appropriate action could become lost in translation, with potentially detrimental outcomes for patients. A recent study reported that healthcare providers report limited knowledge and experience with pharmacogenetic testing and are concerned about the potential misinterpretation of results when integrating pharmacogenetic testing into their workflow 182 . However, they appeared hopeful that pharmacogenetically guided treatment could improve treatment outcomes.…”
Section: Healthcare Practitioner Education and Comfortmentioning
confidence: 99%
“…However, despite the already compiling evidence, especially for SSRIs and tricyclic antidepressants [ 6 , 7 ], pharmacogenetic (PGx) analysis is not yet routinely applied when prescribing these antidepressants. Underlying reasons are diverse and barriers to the implementation of PGx services include fragmentary evidence from prospective clinical trials, limited reimbursement from basic health insurance (which, in Switzerland, is currently only possible if clinical pharmacologists prescribe the specific testing), missing established procedures and, in general, a lack of education and experience among mental health care providers [ 12 , 13 ]. An approach to overcome some of these barriers, to efficiently enable individualized PGx information processing for antidepressant selection and dosing, might involve the interprofessional collaboration of psychiatrists and clinical pharmacists.…”
Section: Introductionmentioning
confidence: 99%